Implementation of an Effective Strategy to Make People Trust the Implementation of COVID-19 Vaccination from an Economic Perspective in Gowa Regency - Mustari, Mustari (Cita konsultindo, 2023)
This research is research with the title Implementation of Effective Strategies to Make People Trust the Implementation of COVID-19 Vaccination from an Economic Perspective. This research aims to find out more about effective strategies for implementing the COVID-19 vaccination in Gowa Regency. The data obtained came from interviews with several informants. This study uses a qualitative method. The research in this article shows that the success of the Covid-19 Vaccination program depends on many factors that influence it, and one of these factors is the strategy in making people believe in Vaccination itself. The level of understanding, participation and knowledge of the community will be positively influenced by planning that is made appropriately, carefully, thoroughly, and with ongoing monitoring and assessment. So if the information conveyed is clear, people will be confident and not confused, and will not need to look for additional sources of information.